Functional-Type Caristi–Kirk Theorem on Menger Space and Application - Soumia Chaira; Mohammed Dahmouni; Abderrahim Eladraoui; Mustapha Kabil (Journal of Mathematics)
In this paper, we extend Caristi’s fixed point theorem in metric spaces to probabilistic metric spaces, and also, we prove some common fixed point theorems for a pair of mappings satisfying a system of Caristi-type contractions in the setting of a Menger space. Two examples are given to support the main results. Furthermore, we have functional equations as an application for the main theorem.